“No Going Back”. A Case Study of Sexual and Gender Minorities in India and their Legal Mobilisation - Kolmannskog, Vikram; Philos, Dr. (Advances in Social Sciences Research Journal, 2016)
This paper explores the legal mobilisation in India against section 377, the anti-sodomy legislation originally introduced by the British. The first part explores the legal mobilisation as experienced by sexual and gender minority activists themselves. In the second part, some themes that have emerged as important are discussed in light of existing research and literature on sexual and reproductive rights lawfare. While the initial decision to litigate was controversial, Indian activists now seem to agree that the impact of litigation has been overall positive. Factors that help explain the Indian case include the particular Indian institution of Public Interest Litigation, engagement on the wider social arena in parallel with the judicial, and positive media attention. Moreover, decriminalization may have been rather easy for everyone in the LGBT/queer community to rally around, regardless of ideological position. In an increasingly polarized India some tensions within the community may become more toxic, however.